PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERINTEGRASI KAHOOT TERHADAP PEMAHAMAN KONSEP FISIKA SISWA MAN ENDE - Rasul Laba; Melkyanus Bili Umbu Kaleka; Aloisius Harso (LPPM Universitas Nias Raya, 2026)
This study aims to determine the effect of implementing the Problem Based Learning (PBL) model integrated with Kahoot! on students’ understanding of physics concepts in Grade XI Science at MAN Ende. The study was motivated by students’ low conceptual understanding, reflected in their difficulty relating physics material to real-life contexts and their limited active participation in classroom learning. This research employed a quasi-experimental method using a one group posttest-only design. The participants were 25 students in the 2025/2026 academic year. The research instrument consisted of 30 multiple-choice questions, including 10 Kahoot-based items and 20 printed items. Data were analyzed using descriptive statistics, a normality test, and a one-sample t-test. The results showed an increase in the mean score from 63.2 to 90.6, with Sig. (2-tailed) < 0.05, indicating a significant positive effect on students’ conceptual understanding of physics.